(untitled) (Herald of the National Children’s Medical Center, 2022)
The aim: evaluating the effectiveness of anesthetic protection of a child during operations on the soft and hard palate (palatoplasty, cheiloplasty) based on the study of hemodynamic parameters in conditions of combined methods of general anesthesia (OA) in combination with sevoHurane. Materials and Methods. A comparative analysis of the studies was carried out in 31 patients, aged from 9 months to 3 years, who were operated on in a planned manner with pathology of the maxillofacial region (cleft palate, cleft lip). Correction of congenital clefts of the lip and palate is a signiKcant part of operations in plastic surgery departments. These patients undergo multi-stage surgical treatment. They often have comorbidities, anemia, and recurrent respiratory infections. Results. The results of the study indicate the advantages of using combined OA + sevoHurane: smooth intraoperative hemodynamic proKle, early recovery of spontaneous breathing with tracheal extubation on the operating table compared to the control group. Conclusions: The combined OA technique (propofol + fentanyl) using the inhalation anesthetic sevoHurane provides effective antinociceptive protection of the child during palatoplasty and cheiloplasty.